Traditional Sutika Paricharya Practices Prevalent in Kozhikode District of Kerala - Aswathy, P; Aravind, S (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Motherhood is the most gifted prize in the world as it is the means of transfer of human generation. Sutika kala (period of puerperium) is the period of happiness as well as the period of complications also. The puerperium is the period from the end of the third stage of labor until most of the patient’s organs have returned to the pre-pregnant state. Proper paricharya is necessary for the maintenance of the health of the puerperal women. There are some traditional practices for the health promotion of Sutika which are prevalent in Kozhikode district of Kerala. The objective of this study is to reveal the scientific background of the traditional Sutika paricharya practices prevalent in Kozhikode. Materials and Methods: The data regarding the Sutika paricharya were collected from the Ayurvedic practitioners from Kozhikode through a Telephonic Survey with the help of a structured questionnaire. Data will be analyzed scientifically and conclusions will be drawn. Results and Discussion: The Traditional Sutika Paricharya practices prevalent in Kozhikode district of Kerala includes the use of Nadi Kashaya, Arista, Nalpamaradi Vethuvellam (water used for bath prepared from Nalpamaradi drugs), Mukkudi, Ullichoru (special rice prepared with onion and its varieties), Pettu lehyam, Thengin pookkuladi lehyam (Avaleha prepared with Inflorescence of coconut), and Navadhanya powder. The details regarding its preparation, uses, effects, and its scientific background were validated and conclusions were drawn. Conclusion: The time-tested and validated scientific practices should be added and updated to the knowledge database of Sutika practices in the Ayurveda system in India.